Intracerebroventricular Coadministration of Protoxin-II and Trace Elements in Rats Enhances the Analgesic Effect of the 1.7 Voltage-Gate Sodium Channel Blocker. (28th December 2019) - Stanciu, Gabriela-Dumitrita; Luca, Andrei; Marza, Aurelia; Alexa-Stratulat, Teodora; Tudorancea, Ionut; Bild, Walther; Rezus, Elena; Rezus, Ciprian; Tamba, Bogdan I.
Abstract : Pain continues to be a global unmet medical need, and the current recommendations for its management require a constant exploration of new drugs that target multiple pain mechanisms, with an improved safety profile and increased treatment adherence. Currently, the enriched distribution and localization within nociceptors of the selective channel blockers and the critical role played by sodium channels in neuronal excitability nominate isoforms as specific targets to generate innovative compounds. In the present report, we verified the hypothesis that coadministration of Protoxin-II, a selective sodium channel inhibitor, and trace elements has direct and improved antinociceptive effects. Groups of seven Wistar rats were treated intracerebroventricularly with a combination of MgCl2, CdCl2, and ZnCl2 and Protoxin-II, respectively, and with Protoxin-II alone (positive) or saline (negative) for controls. Evaluations were performed by nociception assay. Coadministration of these drugs caused an increase in the maximum possible effect of up to 40% as compared with the control groups. Our findings indicate that selective channel blockers continue to be an important nociception target and that the use of trace elements may provide simple but effective means of control over sodium channel blockers' risks, potentially lowering the necessary analgesic doses, thus improving the efficacy and safety profile.